Web-Based Reporting Vulnerabilities System for Cyber Security Maintenance - Hamid Ali, Firkhan Ali; Mohd Sukri, Mohd Khairul Amin; Jali, Mohd Zalisham; AlFatih, Muhammad; Mohd Yusof, Mohd Azhari (semarak ilmu, 2023)
To maintain secure web services and IT infrastructure, this has proposed the prototype of a vulnerability reporting system. Among these reporting systems developed to deal with problems of maintenance and analysis report management system which not yet been implemented in the cyber security scanning tool, Nessus. The system, which was designed to manage and analyze cyber security maintenance by focusing on vulnerability reports, was based on web-based technology. To ensure that the prototyping system could be used quickly, the development process employed the prototyping-rapid application development technique. The administrator of this system may easily manage and keep track of the report following the activity of scanning the cyber security maintenance for vulnerabilities.